Environment-making, cheap-nature, and care : an anthropological study of the Hazel Food, arts, and crafts market in Tshwane - Krige, Detlev (University of Pretoria, 2023)
Dissertation (MSocSci (Social Anthropology))--University of Pretoria, 2022.